UPAYA KANTOR URUSAN AGAMA (KUA) DALAM MEMBIMBING PARA MUALAF MENJADI KELUARGA SAKINAH Study kasus di Kantor Urusan Agama Kecamatan Mojowarno - Ahmad Fajar Ainul Yaqin (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
In general, the term convert is a term for people who have just embraced Islam Islamic religion, and also cannot be separated from various problems or problems faced after become a convert. There are various problems faced by converts to islam coaching to guide them to true Islam. And this is where the Office comes into play Mojowarno District Riligius Affairs (KUA) in developing Muslim convert to be able to do so study the Islamic religion well. This research aims to find out how religious guidance for converts to Islam carried out by the Office of Religious Affairs (KUA) Mojowarno District and find out what problems, probems or abstacles there are carrying out religious guidance for converts to islam carried out by the Affairs Office Religion (KUA) Mojowarno.This research uses field research using qualitative methods. Data collection techniques in this research are interviews, observations, interview. Results from research at the Disrtict Office of Religious Affairs (KUA) Mojowarno pointed out that there are still many converts to islam in the surrounding area Mojowarno which needs religious formation so that in can become a Muslim family in fact, of course we often call it a sakinah, mawaddah, warahmah family.